Pengaruh Good Corporate Governance, Persistensi Laba dan Earning Growth terhadap Kualitas Laba - Benarda Benarda; Desmita Desmita (Universitas Pamulang, 2022)
The purpose of this study was to determine the effect of good corporate governance, earnings persistence and earning growth on earnings quality. This study uses a sample of property, real estate and building construction companies listed on the Indonesia Stock Exchange during the 2015-2019 period. The data used in this research is secondary data. The data obtained and collected are then processed using the Eviews 11 application. The results of this study are jointly independent variables consisting of managerial ownership, institutional ownership, independent board of commissioners, audit committee, earnings persistence and earning growth affect earnings quality. Partially independent board of commissioners affect earnings quality, while managerial ownership, institutional ownership, audit committee, earnings persistence and earning growth have no effect on earnings quality.